Preparation of Gelatin/Carrageenan-Based Color-Indicator Film Integrated with Shikonin and Propolis for Smart Food Packaging Applications - Roy, Swarup; Rhim, Jong-Whan (ACS applied bio materials, 2021)
Gelatin/carrageenan-based functional intelligent film was fabricated by incorporating shikonin and propolis. The shikonin solution extracted from the gromwell (Lithospermum erythrorhizon) root showed excellent pH-responsive color-changing properties in the broad pH range of 2–12 with good gas sensing and color stability properties. The bioactive functional filler materials (propolis and shikonin) were evenly dispersed in the gelatin/carrageenan matrix. The blending of propolis and shikonin enhanced the composite film’s UV blocking property without decreasing much transparency. The mechanical, thermal, and vapor barrier properties of the film were not considerably affected by blending the functional fillers. The addition of propolis and shikonin provided the gelatin/carrageenan composite film with outstanding functional properties (antimicrobial activity and high antioxidant function). The intelligent film was successfully used to monitor the freshness of packaged milk. The intelligent film with functional properties is beneficial in enabling food safety and extending the shelf life of food by monitoring the quality of food.